(untitled) (Hà Nội, 2004)
Contents: Overview and the need of the initiative; The natural and socio-economic features and conservation values of the central Truong Son; Protection and management status...
Keywords: Biodiversity conservation,Bảo tồn đa dạng sinh học; Vietnam,Việt Nam